Adaptation of the hepatitis B virus core protein to CD8+ T‐cell selection pressure. Issue 1 (25th March 2015) - Kefalakes, Helenie; Budeus, Bettina; Walker, Andreas; Jochum, Christoph; Hilgard, Gudrun; Heinold, Andreas; Heinemann, Falko M.; Gerken, Guido; Hoffmann, Daniel; Timm, Joerg
Abstract : Activation of hepatitis B virus (HBV)–specific CD8 T cells by therapeutic vaccination may promote sustained control of viral replication by clearance of covalently closed circular DNA from infected hepatocytes. However, little is known about the exact targets of the CD8 T‐cell response and whether HBV reproducibly evades CD8 T‐cell immune pressure by mutation. The aim of this study was to address if HBV reproducibly selects substitutions in CD8 T‐cell epitopes that functionally act as immune escape mutations. The HBV core gene was amplified and sequenced from 148 patients with chronic HBV infection, and the human leukocyte antigen (HLA) class I genotype (A and B loci) was determined. Residues under selection pressure in the presence of particular HLA class I alleles were identified by a statistical approach utilizing the novel analysis package SeqFeatR. With this approach we identified nine residues in HBV core under selection pressure in the presence of 10 different HLA class I alleles. Additional immunological experiments confirmed that seven of the residues were located inside epitopes targeted by patients with chronic HBV infection carrying the relevant HLA class I allele. Consistent with viral escape, the selected substitutions reproducibly impaired recognition by HBV‐specific CD8 T cells. Conclusion : Viral sequence analysis allows identification of HLA class I–restricted epitopes under reproducible selection pressure in HBV core; the possibility of viral escape from CD8 T‐cell immune pressure needs attention in the context of therapeutic vaccination against HBV. (Hepatology 2015;62:47‐56)